2005
DOI: 10.1111/j.1572-0241.2005.50019.x
|View full text |Cite
|
Sign up to set email alerts
|

Seven versus Ten Days of Rabeprazole Triple Therapy for Helicobacter pylori Eradication: A Multicenter Randomized Trial

Abstract: Seven- and 10-day triple therapies seem equally efficient in peptic ulcer patients. In contrast, 7-day therapy is significantly less effective in nonulcer dyspepsia patients. Ten-day therapy, therefore, seems preferable when treating nonulcer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 46 publications
2
38
0
1
Order By: Relevance
“…Eradication rates of first-line standard therapy reduced from 90% to less than 70-80% (5)(6)(7)(8)(14)(15)(16). Especially resistance to clarithromycin plays a crucial role in the development of inadequate eradication rates and decreases the eradication rates to as low as 70% (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eradication rates of first-line standard therapy reduced from 90% to less than 70-80% (5)(6)(7)(8)(14)(15)(16). Especially resistance to clarithromycin plays a crucial role in the development of inadequate eradication rates and decreases the eradication rates to as low as 70% (17).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the consensus reports also recommend triple therapies consisting of proton pump inhibitor (PPI), clarithromycin and amoxicillin or metronidazole combination for the first-line treatment (2)(3)(4). However, it has been reported that the eradication rates before 2000, which were over 90% (5,6), achieved with the administration of the triple standard therapy, have declined to 70% in the 2000's (7,8). The main reasons for the insufficiency of these regimens are non-compatibility of the patients and gradually increasing antibiotic resistance (clarithromycin and metronidazole resistance).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, several large clinical trials and meta-analysis have shown that the most commonly used firstline therapies -including proton pump inhibitors (PPIs) plus two antibiotics -may fail in up to 20% of patients, 3 and in the clinical routine setting, the treatment failure rate might be even higher. Moreover, during the last few years, several studies have reported 'intention-to-treat' eradication rates lower than 75% [4][5][6][7][8][9][10][11][12] and even lower than 50% 13,14 with PPI-based regimens. Antibiotic resistance to clarithromycin has been identified as one of the major factors affecting our ability to cure H. pylori infection, and the rate of resistance to this antibiotic seems to be increasing in many geographical areas.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, the efficacy of the first-line therapy including proton pump inhibitors plus two antibiotics seems to have decreased, and several studies have reported intention-to-treat eradication rates lower than 75% [1][2][3] and even lower than 50% [4,5] . The resistance to antibiotics is the main cause of H pylori treatment failure.…”
Section: Introductionmentioning
confidence: 99%